Morphometric Aspects of Scad Decapterus macrosoma Bleeker, 1851 in Cape of Salonggar Regency (Jurnal Ilmiah PLATAX, 2018)
This study aims to determine the biological appearance of globe fish that includes size distribution, growth pattern, sex ratio and maturity level of gonad (TKG) in Tanjung Salonggar Melonguane waters of Talaud Islands Regency. Sampling was conducted from May to July 2017. Decapterus macrosoma has found during the study were 268 with total size of 150 - 244 mm and the weight ranged from 34 to 142 grams. Kite fish caught in Tanjung Salonggar has a negative allometric growth type that is the length increase faster than weight gain (b